2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28260
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students Rapidly Learning at Hackathon Events

Abstract: -developed the STEAM Labs TM program to engage middle and high school students in learning science, technology, engineering, arts, and math concepts through designing and building chain reaction machines. He founded and led teams to two collegiate Rube Goldberg Machine Contest national championships, and has appeared on many TV shows (including Modern Marvels on The History Channel and Jimmy Kimmel Live on ABC) and a movie with his chain reaction machines. He serves on the Board of the i.d.e.a. Museum in Mesa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Additionally, prior works have also focused on in-person hackathon events in the context of traditional courses [20,42].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, prior works have also focused on in-person hackathon events in the context of traditional courses [20,42].…”
Section: Introductionmentioning
confidence: 99%
“…In the focus group convened after the end of Project Shhh!, students expressed interest in hackathons--a contest model which requires a lengthy commitment, but that commitment is compressed into one period of time rather than across the semester. While hackathons are intensely concentrated blocks of time, studies have found that students are compelled to apply learning strategies and knowledge and are actively "learning by doing" [5]. In recent years, libraries have sponsored hackathons as events that embody "the spirit" of libraries' commitment to "community, innovation, and outreach" [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The largest accessible group of research participants, undergraduate STEM students, are also the least studied in the literature. Aside from the previous examples, preliminary research in collegiate hackathons has identified small scale knowledge transfer within teams ((La Place et al, 2017)). One of the only mixed-methods approaches confirmed student motivations are centered around learning and networking, but also began to elicit from a small population why some students do not attend hackathons (Warner & Guo, 2017).…”
Section: Hackathonsmentioning
confidence: 99%
“…However, this study was conducted outside of a collegiate environment and does not clarify the development expertise of the participants interviewed which could have ranged from amateur to professional. Previous work on knowledge transfer within collegiate hackathons highlighted some resources participants used, but was limited in understanding the extent of what knowledge was brought into and out of a hackathon and did not address the process in which students worked on projects (La Place et al, 2017).…”
Section: Adaptive Expertisementioning
confidence: 99%
See 1 more Smart Citation